The Concept Of Creativity: Towards An Intergrative Vision Of Creativity In The Psychoeducational Application - Cofii Roger Anoumou; Zbigniew Formella (The Francis de Sales Scientific Society (TNFS.PL), 2022)
Although it is a positive word, always attracting and increasing attention, creativity is a concept that defies definition. As a psychological concept, creativity has resisted unequivocal definition or clear operationalization. Nevertheless, after viewing its etymological and semantic aspects, we focus on some attempts of definitions. As "man's capacity to produce new ideas, insights, inventions or artistic objects, or the act to create something new, to find original solutions, and the willingness to change or transform the world. Creativity has generated numerous definitions with the problem of the lack of consensus among creativity researchers. This seems more complicated when we focus on creativity in cultural context (be the Western or the Eastern one). However, since differences are not deficits, but rather richness that must be complemented, our proposal is to integrate different cultural criteria and offer a unified vision of the concept, which we illustrate referring to Kharkurin's Creativity.4in1 model based on the criteria of Novelty, Utility, Aesthetics and Authenticity. This integrative vision is not yet the last possible attempt, so the call for deeper research and better model is still active.